Green Accounting Practices and Economic Value Added: An Applied Study on Companies Listed on the Qatar Stock Exchange - Al-Dhaimesh, Othman Hel (International Journal of Energy Economics and Policy, 2020)
The purpose of this study is to reveal the reality of green accounting practices and, its effects on economic value-added (EVA) of listed Qatari companies. Content analysis was used to gather study data. the sustainability reports and all other materials related to green accounting subject published by the study sample during the period (2014 - 2019) was deeply viewed. The study applied on seven sectors consists of 47 companies listed in the Qatar exchange selected based on data availability. The study concluded that the quality of green accounting practices in the listed Qatar companies was weak, Was its average in the banking and financial services sector and the telecommunications sector, whereas it’s weak in the insurance and real estate sectors. The study also found that there is a statistically significant effect of green accounting on the EVA of listed Qatari companies. The study also found that there is a statistically significant effect of green accounting on EVA of listed Qatari companies. Moreover, energy, materials, and emissions variables have a negative effect on EVA. Whereas, there is no statistical effect of water variable. Keywords: Green Accounting, Water, Materials, Emissions, Energy, Economic Value-Added. JEL Classifications: Q4, Q53 DOI: https://doi.org/10.32479/ijeep.10199